Respuestas
Respuesta dada por:
23
Sean: x e y tales números:
• x + y = 23 → y = 23 -x
• xy = 102
Entonces: x(23-x) = 102
23x - x² = 102
0 = x² - 23x + 102
0 = (x-17)(x-6)
Si x = 6 → y = 17
Si x = 17 → y = 6
Rpta: Los números son 6 y 17
Saludos!
• x + y = 23 → y = 23 -x
• xy = 102
Entonces: x(23-x) = 102
23x - x² = 102
0 = x² - 23x + 102
0 = (x-17)(x-6)
Si x = 6 → y = 17
Si x = 17 → y = 6
Rpta: Los números son 6 y 17
Saludos!
stevenquito:
tonto
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años